The concept of development in cooperation for development and migratory policies - Azkona, Nerea (Estudios Internacionales, 2013)
It is important to promote synergy between migration and development, as to meet the requirement of a greater coherence of policies, a principle aimed at safeguarding other policies from interfering in the purpose of cooperation. Nevertheless, cooperation is also seen as a tool that can help to stop migratory flows. This global approach has promoted the control of borders and the incorporation of cooperation in migration strategies.